Analisis Pengaruh Kinerja Bank Indonesia Terhadap Pertumbuhan Ekonomi Indonesia - Prima Abi Pangestu; Arya Cembawan Wijaksana; Syafira Febriyanti; Cep Jandi Anwar; Indra Suhendra (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
The purpose of this study is to assess the partial or joint effects of inflation, interest rates, exchange rates, foreign exchange reserves and money supply on Indonesia's economic growth. This study used secondary data from Q1 2015 to Q4 2022. Data analysis included a multiple regression analysis test and a conventional acceptance test. Hypothesis tests include f, t, decision, and correlation tests. At the same time, research results show that independent variables have a large impact on dependent variables. But sometimes inflation, interest rates and foreign exchange reserves do not have a significant impact on economic growth. On the other hand, money supply and exchange rate have a great impact on Indonesia's economic growth.